Evaluation of Index of Cardio-Electrophysiological Balance in Patients With Atrial Fibrillation on Antiarrhythmic-Drug Therapy - Afsin, Abdulmecit; Asoglu, Ramazan; Kobat, Mehmet Ali; Asoglu, Emin; Suner, Arif (Elmer Press Inc, 2021)
Background: Index of cardio-electrophysiological balance (iCEB) has been described as a novel risk marker for predicting malignant ventricular arrhythmia. There remains limited evidence on the effects of amiodarone and propafenone used for sinus rhythm maintenance on iCEB in patients with atrial fibrillation (AF). The aim of this study was to evaluate iCEB in patients with AF on antiarrhythmic-drug therapy. Methods: A total of 108 patients with AF (68 patients using amiodarone and 40 patients using propafenone) and 50 healthy subjects were included in the study. All groups underwent a standard 12-lead surface electrocardiogram. QRS duration, QT, T wave peak-to-end (Tp-e) intervals, iCEB (QT/QRS) and iCEBc (heart rate-corrixted QT (QTc)/QRS) rates were calculated from the electrocardiogram and compared between groups. Results: QT, Tp-e intervals and Tp-e/QT ratio were significantly longer in the amiodarone group than the propafenone and control groups (P < 0.001, for all). iCEB was similar in the amiodarone and control groups (4.4 +/- 0.6 and 4.2 +/- 0.4; P> 0.05), while iCEB values in the propafenone group were significantly lower than the amiodarone group and control groups (3.9 +/- 0.5; P < 0.001). There was a significantly difference in iCEBc values among the amiodarone, control and propafenone groups (4.8 +/- 0.6, 4.6 +/- 0.4 and 4.3 +/- 0.6; P < 0.001, respectively). Conclusions: In this study, higher iCEBc parameters were observed in patients using amiodarone, while iCEBc values were lowest among patients with AF using propafenone. Further studies are needed to determine whether these electrophysiological changes are associated with ventricular arrhythmias for patients with AF on antiarrhythmicdrug therapy.
Keywords: Atrial fibrillation; Antiarrhythmic-drug; Index of cardio-electrophysiological balance; Ventricular arrhythmia